The 2014 World Cup in Natal (Brazil): A study concerning the perception of dwellers (Research, Society and Development, 2017)
Hosting a mega-event promotes transformation in the local’s landscape and impacts the life of its population. Thus, in addition to understanding the important technical issues that guide such interventions, it is essential that research in this field investigate the psychosocial processes involved and the manner in which people perceive these endeavors. The participation of Natal (Brazil) in the 2014 FIFA World Cup brought more than the construction of the Arena das Dunas complex: it changed its own immediate surroundings and the infrastructure of the Metropolitan Region, interfering with the service/equipment structure and urban mobility. Using this context as a starting point, this article investigates the perceptions of residents of the city of Natal about the social and environmental impacts caused by the 2014 World Cup in the city. For this, it focuses on the inhabitants’ perception, the psychological meanings they associate with these changes, and their expectations. The research used a questionnaire, which included socio-demographic data, semantic networks and ten variables associated with socio-environmental changes related to the event: appearance (aesthetics), employment conditions, public space, city image, leisure, urban cleaning, health’s services, urban mobility, public transport and tourism. We interviewed 214 inhabitants aged between 15 and 74 years old who had reached medium or higher education (85%). The data collected showed that: (a) tourism, employment and the image of the city received high evaluation during the 2014 FIFA World Cup and negative evaluations after the event; (b) urban mobility was negatively evaluated at both times; (c) basic services (i.e. health, safety and public transport) obtained the lowest averages; (d) the economically significant categories had a positive evaluation during the event. In the Semantic Web the terms tourism, employment and soccer were the most frequently employed, followed by corruption, violence and expropriations; in addition, the words tourism and employment appeared to be directly associated, which was an expected result due to the media discourse as well as the fact the Natal is a sought-after tourist destination. It was also noted that the participants' perception was associated to their education and their access to information, and that more educated people with access to alternative information channels, such as the Internet, were more critical about the changes. The final discussion explored the relationship between results and broader psychosocial concepts, including attachment to place and place identity.